1994
DOI: 10.1063/1.111457
|View full text |Cite
|
Sign up to set email alerts
|

Observation of the D-center in 6H-SiC p-n diodes grown by chemical vapor deposition

Abstract: Articles you may be interested inHigh quality AlN grown on SiC by metal organic chemical vapor deposition

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
15
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 4 publications
3
15
0
Order By: Relevance
“…The observed energy position and capture cross section of the D level agree well with the reported values of the well known D center, 1,10,11 which has been observed in Bimplanted or B-doped CVD grown SiC. Indeed, electron paramagnetic resonance ͑EPR͒ measurements associate the D center with a boron-vacancy complex.…”
supporting
confidence: 88%
“…The observed energy position and capture cross section of the D level agree well with the reported values of the well known D center, 1,10,11 which has been observed in Bimplanted or B-doped CVD grown SiC. Indeed, electron paramagnetic resonance ͑EPR͒ measurements associate the D center with a boron-vacancy complex.…”
supporting
confidence: 88%
“…The incorporation of the shallow B and Ti has shown to increase with increasing C/Si ratio, which has been explained in terms of site-competition principle sine both types of impurities are believed to occupy Si site [77]. It is also observed that D-center concentration is reduced under C-rich condition for 6H-SiC, which implies the association of a carbon vacancy complex with the D-center [84]. Studies on the microscopic and electronic structure of those defects are still needed to provide further guidance for growth process optimization.…”
Section: Lifetime Control and Measurement For Sic Epilayersmentioning
confidence: 70%
“…Moreover, the recombination which dominates at elevated temperatures with PL peak around 2.10-2.14 eV is related to the well-known D-center. The determination of the energy level of D-center is still in controversial [8,13,14], and there is still lack of direct experimental approach to determine the lattice structure of either the D-center or the D * -center. The possible molecular configurations of the D-center have been predicted by first-principles calculations [15][16][17].…”
Section: Methodsmentioning
confidence: 99%